Literatur Review: Work-Life Balance sebagai Faktor Penentu Produktivitas Karyawan pada Perusahaan Modern - Susanti Angreani; Savira Virsa; Nur Azizah Muchlis; Annisa Maulidya Mustapa; Chris Dayanti Br. Ginting (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Work-Life Balance (WLB) has become a strategic issue in modern human resource management, particularly amid digital transformation, increasing workloads, and the evolution of work patterns. Imbalances between personal life and professional responsibilities may reduce employee well-being and diminish organizational productivity. This study aims to analyze the contribution of WLB as a determining factor of employee productivity through a comprehensive literature review across various organizational contexts. A Systematic Literature Review (SLR) approach was employed by examining published articles from reputable databases such as Scopus, Web of Science, and Google Scholar. The analysis was conducted using content analysis techniques to identify patterns of relationships among variables, moderating and mediating factors, and the relevance of WLB to productivity in multiple sectors. The findings indicate that WLB consistently has a positive effect on employee productivity. WLB enhances work focus, reduces stress, strengthens motivation, and increases employee commitment to the organization. Several indicators including flexible working arrangements, clear leave policies, wellness support, organizational culture, and individual resilience play key roles in achieving work-life balance. Moreover, several studies highlight job satisfaction as an important mediating variable explaining the relationship between WLB and productivity. This study concludes that WLB is a strategic investment for modern companies to improve competitiveness and employee retention. Effective implementation of WLB not only enhances employee well-being but also significantly contributes to organizational performance, efficiency, and long-term sustainability.